Successful management of a benign anastomotic colonic stricture with self-expanding metallic stents: A case report - Guan, Yong-Song (World J Gastroenterol, 2004)
AIM: To assess the effectiveness of and complications associated with metallic stent placement for treatment of anastomotic colonic strictures. METHODS: A 46-year-old man underging two procedures of surgery for perforation of descending colon due to a traffic accident presented with pain, abdominal distention, and inability to defecate. Single-contrast barium enema radiograph showed a severe stenosis in the region of surgical anastomosis and the patient was too weak to accept another laparotomy. Under fluoroscopic and endoscopic guidance, we placed two metallic stents in the stenosis site of the anastomosis of the patient with anastomotic colonic strictures. RESULTS: In this case of postsurgical stenosis, the first stent relieved the symptoms of obstruction, but stent migration happened on the next day so an additional stent was required to deal with the stricture and relieve the symptoms. CONCLUSION: This case confirms that metallic stenting may represent an effective treatment for anastomotic colonic strictures in the absence of other therapeutic alternatives.